Propriedades estruturais e optoeletrônicas de monocamadas de nitreto de boro hexagonal fluoradas - Silva, Deigivan da (2021)
Two-dimensional hexagonal boron nitride (BN) is a semiconductor with a wide bandgap of about 6 eV. The narrowing of such a bandgap is one of the most important and urgent research topics about this material, considering that most of its potential applications in the electronics, optoelectronics and spintronics elds is limited by its large energy gap. Among other possibilities, the inclusion of point defects as well as chemical functionalization using uorine atoms { i.e. uorination, are e ective approaches for tuning the BN bandgap and, therefore, its electronic and optical properties. In addition, these methods can also induce desirable magnetic behavior. In this context, using rst-principles calculations based on the density functional theory (DFT), it has been investigated the structural and optoelectronic properties of fully uorinated BN monolayers (BNF2) as well as the e ect of point defects, namely, anti-sites, substitutional carbon impurities and uorine atom vacancies, in these nanostructures. It has been considered monolayers in both chair-like and boat-like con gurations. The results show that BNF2 nanosheets, for both con gurations, are energetically, mechanically and thermally (at room temperature) stable. The chair-like structures are energetically more stable than the boat-like ones. Besides, these monolayers are semiconductors with an energy gap of the order of 3 eV, are nonmagnetic, have high transmissivity and present absorption and conduction just in the ultraviolet (UV) region. The uorinated nanosheets including an anti-site have an energy gap varying in the range 1.19{2.24 eV and they also do not present any magnetic moment. On the other hand, uorinated monolayers incorporating a carbon impurity or a uorine atom vacancy are metallic and they exhibit a net magnetic moment of 1 B. In short, the introduction of the above-mentioned point defects substantially modi es the optical properties of BNF2 monolayers in the low energy region (<4.0 eV) where, among other e ects, absorption and conduction can be induced in the whole infrared and visible regions, depending upon the defect.